Representasi Kearifan Pengetahuan Setempat (Local Knowledge) Suku Sasak dalam Wasiat Renungan Masa Pengalaman Baru Karya TGKH. Zainuddin Abdul Majid - Hendra Gunawan; Mardani Mardani (Departement of Mathematics Education, 2024)
The wisdom possessed by the Sasak tribe is a potential that must be considered. Its existence for every member of the Sasak tribe is a gift that always provides its own color. Focusing on this research, the researcher examines the representation of local knowledge of the Sasak Tribe in the Wasiat Renungan Masa Pengalaman Baru by TGKH. Zainuddin Abdul Majid. The aim of carrying out this research is to explore and describe the local wisdom of the Sasak tribe which originates from the Wasiat Renungan Masa Pengalaman Baru.. The method in this research uses qualitative research, literature study. The data in this research is in the form of WRMPB text. The data source in this research is the WRMPB book or manuscript by Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid. In this case, the researcher becomes the main instrument, using data cards. The data collection technique used is documentary study. Next, analyze the data by organizing it, sorting it into manageable units, synthesizing it, looking for and finding patterns, finding what is important and what has been learned, and deciding what can be told to others. Checking the validity of the data in this study used triangulation techniques. In the local wisdom of the Sasak tribe, there are 7 verses of the New Experience Period Renunagan's Will which represent the wisdom of knowledge of the Sasak tribe. The 43rd verse is part 1. The 44th verse is part 2. The 39th verse is part 2. The 134th verse is part 1. The 18th verse is part 1. The 186th verse is part 1, and the 180th verse is part 1.